2014
DOI: 10.1007/s00726-014-1810-3
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein supplementation accelerates satellite cell proliferation during recovery from eccentric exercise

Abstract: Human skeletal muscle satellite cells (SCs) are essential for muscle regeneration and remodeling processes in healthy and clinical conditions involving muscle breakdown. However, the potential influence of protein supplementation on post-exercise SC regulation in human skeletal muscle has not been well investigated. In a comparative human study, we investigated the effect of hydrolyzed whey protein supplementation following eccentric exercise on fiber type-specific SC accumulation. Twenty-four young healthy su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 50 publications
6
61
2
3
Order By: Relevance
“…Olsen et al first demonstrated that chronic resistance exercise training (RET) with protein supplementation may provide a slight enhancement of the satellite cell pool compared to RET alone (32). Based on basic science and pre-clinical findings, we anticipated that protein supplementation would enhance satellite cell activity and content through mTORC1 (17, 40) and particularly on MHC II fibers (1, 11). Instead, we demonstrated similar increases in satellite cell content between treatments, which were driven primarily through increases in MHC II fibers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Olsen et al first demonstrated that chronic resistance exercise training (RET) with protein supplementation may provide a slight enhancement of the satellite cell pool compared to RET alone (32). Based on basic science and pre-clinical findings, we anticipated that protein supplementation would enhance satellite cell activity and content through mTORC1 (17, 40) and particularly on MHC II fibers (1, 11). Instead, we demonstrated similar increases in satellite cell content between treatments, which were driven primarily through increases in MHC II fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is that physiological adaptation may best explain the insensitivity to protein supplementation typically seen in chronic exercise studies. Farup and colleagues demonstrated that whey protein supplementation following eccentric exercise accelerated the satellite cell pool expansion compared to consumption of carbohydrate placebo (11). However, by 168 hr post exercise (11) and after 12 weeks of training (12) the satellite cell pool was identical between treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type II fiberassociated enhancement of satellite cell content and activation (as reflected by DLK1 expression) has been observed in young recreationally active men 1-3 days following an acute bout of maximal unilateral isolated eccentric exercise or traditional resistance-type exercise. [112][113][114][115] Resistance exercise training can also increase satellite cell content in young and aged men and women, 113,[116][117][118][119] and the increase has been demonstrated to be specific to type II fibers in elderly men and correlated with fiber size or muscle volume in young and aged men. 120,121 The strong relationship between satellite cell content and muscle fiber size postexercise would suggest a role for the satellite cell in growth, yet myonuclear accretion and/or new fiber synthesis are not consistently observed posttraining.…”
Section: The Resident Progenitor Cell In Skeletal Muscle and Its Respmentioning
confidence: 96%